Abdominal Surgery A Brief Overview - Zaghal, Ahmad; El Rifai, Arwa (IntechOpen, 2021)
This book presents a brief overview of the main issues related to abdominal surgeries in adults and children. It provides readers with the cognitive and technical knowledge necessary for taking care of patients who have undergone abdominal surgeries. It also presents a summary of the indications, some technical considerations, and possible complications of abdominal surgeries.